Association between otolin-1 and benign paroxysmal positional vertigo: A meta-analysis - Liu, Xiaoxia; Han, Kun; Zhou, Min; Wu, Yunqin (Frontiers in Neurology, 2022)
Abstract Background: Research on the potential of inner ear proteins as serum biomarkers for the diagnosis and prognosis of various inner ear diseases is growing. Among them, benign paroxysmal positional vertigo (BPPV) is the most common vestibular disease. Notably, otolin-1 is an inner ear specific protein that is detectable in blood serum. Thus, this meta-analysis was conducted to determine the relationship between otolin-1 and BPPV. Methods: This meta-analysis was conducted by searching the PubMed, EMBASE, Cochrane Library, Google Scholar, and China Network Knowledge Infrastructure databases for eligible original studies in Chinese or English published between January 2010 and February 2022. Data were collected and pooled by using mean differences (MDs) with corresponding 95% confidence intervals (CIs). Heterogeneity among the studies was then assessed using I2 statistics and the adopted fixed- or random-effect mode. Egger’s and Begg’s tests were also used to assess publication bias. Results: Six articles with a total of 585 participants were included. Serum otolin-1 levels were remarkably increased in patients with BPPV as compared to that in healthy controls (MD: 165.38, 95% CI: 110.13–220.64, p < 0.00001). Egger’s and Begg’s tests indicated no publication bias, and results were reliable based on sensitivity analysis. Conclusions: This meta-analysis indicated that there was a higher level of otolin-1 in patients with BPPV than in healthy controls. Otolin-1 may therefore serve as a biomarker for the onset of BPPV.